EDUKASI PROTOKOL KESEHATAN DAN STRATEGI PEMASARAN ONLINE UMKM MASYARAKAT DI WILAYAH KELURUHAN MAYANGAN KOTA PASURUAN DIERA PANDEMI COVID19 - Yufenti Oktafiah; Sri Hastari; Dwita Laksmita (Bajang Institute, 2022)
The COVID-19 pandemic has had a wide impact on various fields, including small and medium-sized businesses. The solution to the existing problems is through educational activities about health protocols for adapting new habits in business premises in the era of the Covid-19 pandemic, socialization about processing management and product marketing strategies and product packaging, and online marketing training through social media. The results of the service activities carried out showed an increase in partner knowledge about health protocols in the place of business by 100%, processing management and marketing strategies by 80%, and an increase in partner knowledge and skills in online marketing by 70%.